The A–Z of Zika drug discovery. Issue 11 (November 2018) - Mottin, Melina; Borba, Joyce V.V.B.; Braga, Rodolpho C.; Torres, Pedro H.M.; Martini, Matheus C.; Proenca-Modena, Jose Luiz; Judice, Carla C.; Costa, Fabio T.M.; Ekins, Sean; Perryman, Alexander L.; Horta Andrade, Carolina
Highlights: Recent advances in Zika virus drug discovery efforts. Drug repositioning and computationally guided compounds. New inhibitors and promising ZIKV molecular targets. Promising host cell targets for ZIKV drug design. Lessons learned from ZIKV drug discovery. Abstract : Despite the recent outbreak of Zika virus (ZIKV), there are still no approved treatments, and early-stage compounds are probably many years away from approval. A comprehensive A–Z review of the recent advances in ZIKV drug discovery efforts is presented, highlighting drug repositioning and computationally guided compounds, including discovered viral and host cell inhibitors. Promising ZIKV molecular targets are also described and discussed, as well as targets belonging to the host cell, as new opportunities for ZIKV drug discovery. All this knowledge is not only crucial to advancing the fight against the Zika virus and other flaviviruses but also helps us prepare for the next emerging virus outbreak to which we will have to respond. Teaser: Zika clinical outcomes might be nefarious impacting newborns for a lifetime. There is still no drug available to cure Zika. We provide guidance to help understand and advance the search for a cure.